(untitled) (TAJ: Journal of Teachers Association, 2011)
Bloody pleural effusion may be a clinical complication of many diseases like malignancy, trauma, pulmonary infarction, ovarian pathology, certain infections etc. Rarely pulmonary, endometriosis can present with haemothorax & pose a diagnostic problem to clinicians. Histopathological confirmation is difficult, since bleeding site is not easy to locate. However, a presumptive diagnosis of pulmonary endometriosis can be made with a typical clinical history. We report a case of pleural endometriosis in a 28 years infertile lady presented with catamenial haemothorax occurring in the first 3 days of menstruation over a 3 months period associated with right shoulder pain & progressive shortness of breath for last 6 years. She was treated with continuous low dose oral contraceptive pill & there was no evidence of recurrent haemothorax during 9 months of follow up period. doi: 10.3329/taj.v19i1.3165 TAJ 2006; 19(1): 27-30